TRANSFORMASI ESTETIK SENI KRIYA; KELAHIRAN DAN KRIYA MASA KINI - Zam, Riswel; Dharsono, Dharsono; Raharjo, Timbul (Gorga : Jurnal Seni Rupa, 2022)
This paper discusses the aesthetic transformations in craft art.  The discussion focuses on craft art as a form of socio and cultural bonding in the past that developed into a part of individual culture and a means of self-expression in the present.  Studies are conducted on aesthetic components, such as the form, purpose, and expressive content found in crafts.  To achieve the goals, studies in the form of qualitative research using cultural and artistic methods are employed.  According to the research, craft art is ingrained in human life and has existed from prehistoric times to the present.  The philosophy that guided the development of ancient crafts is founded on a metaphysical perspective, a charge of spiritual, religious, and magical principles that form works of high quality crafts and reflect the soul of their era.  The philosophy that guided the development of ancient crafts is founded on a metaphysical perspective, a charge of spiritual, religious, and magical principles that form works of high quality crafts and reflect the soul of their era.  Modern or contemporary craft art, which displays aesthetic inclinations as a result of the interaction and effect of freedom of expression, is currently referred to as art craft.  The thought and philosophy of art also influenced the creation of crafts, by adapting of understanding Western™s fine art to the archipelago's cultural norms. These adaptations and acculturations make craft art a manifestation that is affected and reflects societal changes that occur in Indonesia or along with the soul of the times.   Keywords: aesthetic transformation, art craft. AbstrakTulisan ini membahas transformasi estetik dalam seni kriya. Pembahasan difokuskan pada seni kriya sebagai ikatan sosio-kultural pada masa lampau yang berkembang ke dalam aspek individu-kultural sebagai media ekspresi personal pada saat ini.  Kajian dilakukan terhadap unsur-unsur estetik yang meliputi bentuk, fungsi, dan muatan ekspresi yang terkandung dalam kriya. Untuk mencapai tujuan digunakan kajian berupa penelitian kualitatif melalui pendekatan kebudayaan dan pendekatan estetik. Temuan yang diperoleh adalah bahwa seni kriya melekat dan berjalan seiring dengan kehidupan manusia sejak masa prasejarah sampai sekarang. Penciptaan kriya masa lampau dilandasi oleh filosofi yang berorientasi pada pola pikir metafisis, muatan nilai-nilai spiritual, religius, dan magis yang menghasilkan karya-karya kriya adiluhung dan mencerminkan jiwa zamannya. Sementara seni kriya modern atau kontemporer menunjukkan kecenderungan estetik sebagai interaksi dan pengaruh kebebasan berekspresi, kriya ini dikenal dengan kriya seni. Pemikiran dan filsafat seni juga memberi pengaruh pada penciptaan kriya, dengan mengadopsi aliran-aliran seni rupa Barat yang disesuaikan dengan kebudayaan nusantara. Penyesuaian dan akulturasi tersebut menjadikan seni kriya sebagai manifestasi kesenian yang dipengaruhi serta mencerminkan perubahan-perubahan sosial yang terjadi di Indonesia atau seiring dengan jiwa zaman.Kata Kunci:transformasi estetik, seni kriya. Authors:Riswel Zam : Institut Seni Indonesia PadangpanjangDharsono : Institut Seni Indonesia SurakartaTimbul Raharjo : Institut Seni Indonesia Yogyakarta References:Adryamarthanio, V. (2022). Batik Pesisir: Sejarah, Ciri-ciri, dan Motif. https://kompas.com/stori/read/2022/04/27/090000579/batik-pesisir--sejarah-ciri-ciri--dan-motif (diakses tanggal 1 November 2022).Ahmad, A. S. E. (2021). Kritik Sejarah Batik Sidoarjo. Gorga¯: Jurnal Seni Rupa, 10(1), 137. https://doi.org/10.24114/gr.v10i1.24626.Burhan, M. A. (1999). Nilai Estetik dalam Seni Lukis di Indonesia. Jurnal Seni, ISI Yogyakarta., VI(3).Dharsono, D. (2016). Kreasi Artistik, Perjumpaan Tradisi Modern dalam Paradigma Kekaryaan Seni. Yogyakarta: Citra Sains.Dillistone, F. (2002). The Power of Symbols. Jakarta: Penerbit Kanisius.Feldman, E. B. (1967). Art As Image and Idea. USA: Prentice Hall.Gie, T. L. (2004). Filsafat Seni: Sebuah Pengantar. Yogyakarta: Pusat Belajar Ilmu Berguna.Guntur, G. (2021). Kriya Retro, Biutifikasi dan Legatimasi Artistik. Yogyakarta: Pusat Belajar Ilmu Berguna.Gustami, S. (2007). Butir-butir Mutiara Estetika Timur, Ide Dasar Penciptaan Seni Kriya Indonesia. Yogyakarta: Prasista.Joedawinata, A. (2001). Seni Kriya dan Desain di Lingkungan Perguruan Tinggi. Jurnal SR&D Fakultas Seni Rupa Dan Disain ITB, Bandung, 1.Junaedi, D. (2016). Estetika Subjek, Objek, dan Nilai. Yogyakarta: ArtCiv.Kamal, M. N. (2020). Kerajinan Perak Tinjauan Pada Proses Dan Makna Simbolis Ornamen Di Home Industry Di Koto Gadang. Gorga¯: Jurnal Seni Rupa, 9(2), 409. https://doi.org/10.24114/gr.v9i2.21229.Kartika, D. S. dan N. G. P. (2004). Pengantar Estetika. Yogyakarta: Rekayasa Sains.Marianto, M. D. (2011). Menempa Quanta Mengurai Seni. Yogyakarta: Badan Penerbit ISI Yogyakarta.Najoan,Stephanie Jill., J. C. M. (2011). Transformasi Sebagai Strategi Desain. Media Matrasain, 8(2), 117“130. https://doi.org/https://doi.org/10.35792/matrasain.v8i2.330Nugraha, A. (1999). Kriya Indonesia, Sebuah Wilayah Sumber Inspirasi Yang Tak Terbatas. Yogyakarta: Prasista.Ponimin, & Guntur. (2021). The COVID-19 War in Ceramic Arts: Navigating Aesthetic and Symbolic Expressions. Aisthesis. Pratiche, Linguaggi e Saperi Dell™estetico, 14(1), 81“99. https://doi.org/10.36253/aisthesis-12056.Raharjo, T. (2011). Seni Kriya dan Kerajinan. Yogyakartaa: Program Pascasarjana Institut Seni Indonesia Yogyakarta.Sakti, Z. (2017). Pengertian Unsur Estetika dan Unsur Ergonomis Produk Kerajinan. https://www.aelilmu.com/2017/09/pengertian-unsur-estetika-dan-unsur-ergonomis-produk-kerajinan-html (diakses tanggal 1 November 2022).Soedarso. (2006). Trilogi Seni; Penciptaan, Eksistensi, dan Kegunaan Seni (Cetakan Pe). Yogyakarta: BP ISI Yogyakarta.Strauss, A. dan J. C. (2007). Dasar-dasar Penelitian Kualitatif. Jakarta: Pustaka Pelajar.Sullivan, L. (1896). Number BY. Lippincott´s, 403“409.Sunarto, K. (2004). Pengantar Sosiologi (Revisi). Jakarta: Lembaga Penerbitan Fakultas Ekonomi Universitas Indonesia.Zam, R. (2006). Cerek dalam Ekspresi Kriya Logam. Yogyakarta: Institut Seni Indonesia Yogyakarta.Zam, R., & Ferawati, F. (2020). POTENSI DAN PELUANG PENGEMBANGAN KERAJINAN COR KUNINGAN SUNGAI PUAR DALAM ERA REVOLUSI INDUSTRI 4.0. Artchive: Indonesia Journal of Visual Art and Design, 1(1), 46. https://doi.org/10.53666/artchive.v1i1.1561.Zuhdi, B. M. (2010). PERKEMBANGAN KONSEP KRIYA. Imaji, Fakultas Bahasa dan Seni, 1(1). https://doi.org/10.21831/imaji.v1i1.142.